Chimney Thoracic Endovascular Aortic Repair (Tevar) in Stanford Type B Aortic Dissection Patient: First Time Procedure in Manado - Paat Rigel; Tamburian Christha; Sukanto Wega; Tangkilisan Adrian; Satriadi Wayan (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Aortic dissection is a cardiovascular emergency characterized by a tear in the aortic intima layer and the formation of a false lumen, posing risks of fatal complications such as rupture and organ malperfusion. Stanford type B dissections may be managed conservatively; however, complicated cases require intervention. Thoracic Endovascular Aortic Repair (TEVAR) has emerged as the preferred modality, offering lower perioperative morbidity and mortality compared to open surgery. To report the first TEVAR procedure performed in Manado on a patient with Stanford type B aortic dissection, highlighting the technical approach, operative challenges, and clinical outcomes. A 62-year-old male with a history of hypertension and chronic chest pain was referred following a CT angiography that revealed a Stanford type B aortic dissection with an entry site in the proximal descending aorta. TEVAR was performed with stent-graft placement in zone 2 and a chimney graft to preserve perfusion of the left subclavian artery (LSA). Intraoperative aortography confirmed false lumen exclusion without endoleak. The patient showed significant clinical improvement and recovered without postoperative complications. The procedure was technically and clinically successful, with no major complications. Postoperative evaluation confirmed stable stent position and maintained LSA perfusion. This case demonstrates that TEVAR can be safely implemented in non-tertiary regional hospitals with thorough preparation. The first TEVAR procedure in Manado illustrates that this technique can be an effective solution for complicated type B aortic dissections. This experience marks a milestone in the development of endovascular services in resource-limited settings and may serve as a reference for similar institutions in Indonesia.